Fall Prevention: Solutions for Your Home - Emily Beardsley; Leigh Nova; Linda Benjamin Bobroff; Wendy Lynch (EDIS)
One in three adults 65 and older experience a fall each year. 60% of falls occur in the home. There are changes you can make to reduce your personal fall risk while meeting your personal needs